(untitled) (Global Journal of Science Frontier Research, 2015)
There is continued demand for new varieties to satisfy the needs of farmers in Uganda for different production regions or agro ecological zones. Despite release of several improved high yielding varieties by National Agriculture Research Organization, farmers in South Western Agro-Ecological Zone have continued to rely on landraces whose production adversely is affected by both biotic and abiotic stresses. Besides, most landraces grown are white fleshed with traces of Beta-carotene. Mbarara Zonal Agriculture Research and Development Institute identified eleven sweet potato varieties, some of which orange-fleshed rich in beta carotene, to evaluate the in the zone and subsequent promotion. All the improved varieties evaluated were high yielding (11-20 t/ha) and their palatability and sensory tastes were not different from the farmer preferred local check Nderera.